2020
DOI: 10.3389/fpsyt.2020.00083
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Difference in Quantitative Electroencephalography Variables Between Responders and Non-Responders to Low-Frequency Repetitive Transcranial Magnetic Stimulation in Depression

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is an effective treatment for depressive disorder, with outcomes approaching 45-55% response and 30-40% remission. Eligible predictors of treatment outcome, however, are still lacking. Few studies have investigated quantitative electroencephalography (QEEG) parameters as predictors of rTMS treatment outcome and none of them have addressed the source localization techniques to predict the response to low-frequency rTMS (LF rTMS). We investigated electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 92 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…When people get stressed about life, the mPFC goes into overdrive. [21][22][23][24] Another brain region associated with depression is the amygdala, or "fear center." This part of the brain is responsible for the fight-or-flight response, which triggers the adrenal glands to release the stress hormone cortisol in response to fear and perceived danger.…”
Section: Depressive Episodesmentioning
confidence: 99%
“…When people get stressed about life, the mPFC goes into overdrive. [21][22][23][24] Another brain region associated with depression is the amygdala, or "fear center." This part of the brain is responsible for the fight-or-flight response, which triggers the adrenal glands to release the stress hormone cortisol in response to fear and perceived danger.…”
Section: Depressive Episodesmentioning
confidence: 99%
“…However, there was no significant change in the frontal EEG alpha asymmetry. More recently, Vlcek et al [ 79 ] investigated whether there were different frontal asymmetry patterns between low-frequency rTMS (LF rTMS) responders and nonresponders. The results showed that there was no significant difference in frontal EEG alpha asymmetry in the resting state between LF rTMS responders and nonresponders.…”
Section: Frontal Eeg Alpha Asymmetry In the Resting State And Antidep...mentioning
confidence: 99%
“…Therefore, QEEGt keeps the temporal resolution of EEG and incorporates the necessary anatomic or space resolution provided by MRI. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Using QEEGt, this study compares the critical neural correlates of subjects remembering two separate altered states of consciousness, near-death experience (NDE) and spiritual contemplative experience (SCE), a.k.a. mystical experience.…”
Section: Introductionmentioning
confidence: 99%